GAME THEORY APPLICATION IN DECISION MAKING OF HORTICULTURE FARMING - Putri Budi Setyowati; Hery Toiba; S Sujarwo; S Syafrial; Condro Puspo Nugroho (Agricultural Socio-Economics Journal, 2021)
In running farming system, farmers not only have a role important as owners who land they farm. But also they are as farm managers to make any decisions to face their farming problems under risk and uncertainty. These problems are categorized as internal and external factors related to price fluctuations of agricultural commodities. For that reason, farmers need to consider some strategies to overcome their farming problem for instance by choosing the best commodities that would give them an optimal profit. The maximax, maximin, savage, and laplace criterions were used to analyze decision making of horticulture farmer in determining which best horticultural commodities to plant according to their behaviour and attitude toward farming risk. Thus, horticulture farmer will be able to make a choice whether or not it is potato, cabbage, or, scallion that will be cultivated in the next planting period. Potato farmers are categorized as the optimistic farmer who loves farming risks and they are cautious. While scallion farmers are pessimistic farmers and they are risk averse. In addition, cabbage farmers are the ones who have the least regret.